Risk factors of impaired humoral response to COVID-19 vaccination in rituximab-treated patients. Issue Volume 61:Issue S12(2020) (2nd November 2021) - Avouac, Jérôme; Miceli-Richard, Corinne; Combier, Alice; Steelandt, Alexia; Fogel, Olivier; Mariaggi, Alice Andrée; Meritet, Jean-François; Rozenberg, Flore; Molto, Anna; Allanore, Yannick
Abstract: Objective: To identify which factors influence humoral response to coronavirus disease 2019 (COVID-19) vaccination in rituximab (RTX)-treated patients. Methods: This was an observational, prospective, usual care study including consecutive patients with inflammatory rheumatic diseases in maintenance therapy with RTX. All patients received a two-dose regimen COVID-19 vaccination. Serum IgG antibody levels against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) spike proteins were measured at the time of the new RTX infusion. Results: From the recruited patients, 16/45 (36%) produced antibodies reaching the assay cut-off value of 15 AU/ml and 29/45 (64%) had a negative serology. Within RTX-treated patients, 25 (56%) had undetectable B cells. Negative serology was associated with undetectable B cells (24/25 vs 5/20, P < 0.001). Moreover, SARS-CoV-2 spike antibodies correlated with CD19 counts (r = 0.86, P < 0.001). The effect of RTX and MTX was additive in terms of seroconversion rates (23% vs 50% in patients receiving RTX in monotherapy, P = 0.12) and SARS-CoV-2 spike antibody levels [3.80 (95% CI 3.80, 7.50) vs 75 (95% CI 3.8, 353) AU/ml in patients receiving RTX in monotherapy; P = 0.025]. Multivariate analyses including demographics, disease characteristics, gammaglobulin levels, RTX and other therapies used, CD19 counts, and the time between the last RTX infusion and vaccination identified detectable B cells as the only variable independently associated with seropositivity [odds ratio 35.2 (95% CI 3.59, 344.20)]. Conclusions: B cell depletion is the main independent contributing factor of antibody response to SARS-CoV-2 vaccination in RTX-treated patients. Monitoring CD19 may be of interest to identify the most appropriate period to perform vaccination.